Person-job fit, person-organization fit, proactive personality and career success: The mediating role of job performance - Yahya, Khulida Kirana; Tan, Fee Yean; Othman, Siti Zubaidah; Pangil, Faizuniah; Mat, Norsiah; Mat, Norazuwa (Universiti Utara Malaysia, 2012)
This study examines three factors namely person job fit, person-organization fit and proactive personality that might influence career success. Job performance is also tested as mediator in the relationship between person-job fit, person-organization fit, proactive personality and career success. 180 technical employees from 10 MSC status companies located in Kedah and Penang participated in this study.Research objectives were tested using correlation and regression analyses.Based on the correlation analysis, the results indicate that all the independent variables tested in this study which includes person-job fit, person-organization fit and proactive personality were positively related with career success and with job performance.Job performance was also found positively related to career success.However, results from the regression analysis showed that job performance has no mediating effect on the relationship between person-job fit, person organization fit, proactive personality and career success. The empirical findings derived from this study can be used as a basis in planning for employees’ career success and job performance.Based on the present findings, organization should emphasize on such attributes like proactive personality, and person job fit to ensure career success.Nonetheless, all three independent variables specifically proactive personality, person-job fit and person organization fit are important in enhancing employees’ job performance. Recommendations for future studies and limitations of the present study are also discussed.